Transcriptome sequencing reveals differences between leydig cells and sertoli cells of yak - Wang, Yaying; Pan, Yangyang; Wang, Meng; Afedo, Seth Yaw; Zhao, Ling; Han, Xiaohong; Liu, Minqing; Zhao, Tian; Zhang, Tongxiang; Ding, Tianyi; Wang, Jinglei; Cui, Yan; et al. (Frontiers in Veterinary Science, 2022)
In this study, we detected the expression of mRNAs, lncRNAs and miRNAs in primary cultured LCs and SCs of yak by RNA sequencing technology. A total of 84 differently expression mRNAs (DEmRNAs) (LCs vs. SCs: 15 up and 69 down), 172 differently expression lncRNAs (DElncRNAs) (LCs vs. SCs: 36 up and 136 down) and 90 differently expression miRNAs (DEmiRNAs) (LCs vs. SCs: 72 up and 18 down) were obtained between two the types of cells. GO enrichment and KEGG analysis indicated that the differently expression genes (DEGs) were more enriched in the regulation of actin cytoskeleton, Rap1/MAPK signaling pathway, steroid biosynthesis, focal adhesion and pathways associated with metabolism. Targeted regulation relationship pairs of 3β-HSD and MSTRG.54630.1, CNTLN and MSTRG.19058.1, BRCA2 and MSTRG.28299.4, CA2 and novel-miR-148, and ceRNA network of LAMC3-MSTRG.68870.1- bta-miR-7862/ novel-miR-151/novel-miR-148 were constructed by Cytoscape software. In conclusion, the differences between LCs and SCs were mainly reflected in steroid hormone synthesis, cell proliferation and metabolism, and BTB dynamic regulation, and 3β-HSD, CNTLN, BRCA2, CA2 and LAMC3 may be the key factors causing these differences, which may be regulated by ncRNAs. This study provides a basic direction for exploring the differential regulation of LCs and SCs by ncRNAs.